Sarah : HRH, The Duchess of York : A Biography - Seward, Ingrid (London Fontana, 1992)
From her divorce-torn childhood and early life in jet-set London and Switzerland to the Cinderella romance that thrust her into the limelight, Fergie presents the incomparable, charming, down-to-earth, warm, boisterous, provoc ative Duchess of York. 8 pages of color photographs. Martin's.
Include Illustrations and Index.
An intimate biography of the exuberant, inimitable Fergie. The author charts her growing-up, her early loves and the romance with Andrew. She goes on to look at her friendship with Diana, the wedding, the tours, her relationships with the rest of the Royal Family and her reaction to the press.
Keywords: Sarah, Duchess of York -- Nobility -- Great Britain